Chronic total occlusion percutaneous coronary intervention in prior coronary artery bypass graft surgery patients: Caveat Emptor!. Issue 1 (7th January 2022) - Simsek, Bahadir; Brilakis, Emmanouil S.
Key Points: Stable angina patients with prior coronary artery bypass graft surgery (CABG) who underwent chronic total occlusion percutaneous coronary intervention (CTO PCI) in England and Wales between 2007 and 2014 had more complex clinical and angiographic characteristics, lower success, similar incidence of periprocedural complications, and higher mortality at follow‐up compared with patients who had not had prior CABG. After adjustment, CTO PCI in prior CABG patients was associated with 66% lower success rates, but similar risk of periprocedural complications and mortality at follow‐up. CTO PCI in prior CABG patients can be very challenging, is subject to unique complications and risks, and should be undertaken with caution by experienced operators.